The Effect of Family Literacy on Students' Interest in Reading - Octavian Muning Sayekti; Imam Khoirudin; Chiang Yi Ying (Jurnal Prima Edukasia, 2023)
Interest in reading among children in Indonesia is still at a low level. Low reading interest requires supporting factors that can influence reading interest. The purpose of this study was to examine the effect of family literacy on students' reading interest. This study uses a type of quantitative research with the type of ex post facto. Data collection techniques using observation and questionnaires. The analysis used in this research is an analysis using descriptive associative research. In this study the statistical technique used is simple linear regression analysis. Simple linear regression is used only for one independent variable and one dependent variable. The results of the research show that family literacy has an influence on students' interest in reading. Evidenced by the t test which shows the number 5.245. From the results of the t test which shows that the family literacy variable partially influences the variable interest in reading with a significance level of 0.000. The results of the determinant test showing the influence of family literacy on reading interest is the R result of 0.258